Análise epidemiológica e espacial, dos casos novos de tuberculose em Feira de Santana-Ba, no período de 2005 -2016 - Rodrigues, Roquenei da Purificação (2018)
Tuberculosis is one of the oldest infectious diseases in the world and currently represents a public health problem worldwide, although there are technological resources capable of promoting the control of this disease. This demonstrates that tuberculosis crosses biological barriers, since it is linked to living, sanitary and economic conditions, and control and treatment actions must be intersectoral. The objective of this study was to analyze the epidemiological profile and spatial distribution of new cases of tuberculosis in Feira de Santana, Bahia, between 2005 and 2016. This is an epidemiological, descriptive, historical series , with a study design aggregated by neighborhoods and rural districts, using secondary data from the Information System of Notifiable Diseases, referring to the new cases of tuberculosis, between the years 2005-2016, in the municipality of Feira de Santana - Bahia. This work was composed in 9 steps: bibliographic survey; data collect; structure of the database; data analysis; characterization and epidemiological analysis; spatial analysis and association with socioeconomic factors, elaboration of results and discussion and final considerations. Between the years 2005-2016, there were 2,266 new cases of tuberculosis reported. As for the socio-demographic characterization, it was verified that the highest percentage of the individuals was between 20 -34 years old (31.5%); the most affected were males (65.5%) and race / color, those who declared themselves to be brown (54%). Regarding the clinical aspects, 83.7% corresponded to the pulmonary form of the disease. As regards the spatialisation of the average incidence, it was observed that the occurrences were more concentrated in the central districts: Capuchinhos, Getúlio Vargas Park, Central Point, Center, New Street and Sobradinho and in the peripheral areas: Aviário, Subaé, Santo Antônio dos Prazeres, Novo Horizonte and Pampalona. In what concerns the rural districts, the one that had more average incidence was the district Governor Dr. João Durval Carneiro. The results of this study evidenced the importance of epidemiology and spatial analysis in a joint way, for a better organization of surveillance strategies and organization of health services for tuberculosis control